(untitled) (Journal of the College of Basic Education, 2022)
The research aims to conduct a practical study of the effects of atmospheric factors on the propagation of the laser beam in the atmosphere, through the design and construction of a laboratory measurement container and the study of analyzing the effect of attenuation and absorption factors due to dust and relative humidity. Lasers with visible and invisible wavelengths (0.53, 0.632, 0.81, 1.05) µm were used.With a diffusion length of (7.5 m) inside the container with dimensions (1.5 x 0.4 x 0.6) m-3. The results showed that the atmosphere attenuates the optical signal when the light is absorbed and scattered by the particles in its path with sizes (40-60) µm. The attenuation coefficient was calculated By calculating the absorption coefficient and scattering coefficient for all particle sizes above.